Understanding the other : an introduction to Christian and Jewish relations - Beyers, Jaco, 1971- (African Sun Media, 2017)
In a religious pluralistic society the other cannot be ignored, even less so when there is a familial relationship between religions. The way in which Judaism and Christianity relate can be conceptualised in many different forms, depending on the theory one subscribes to. Did Judaism and Christianity derive from a common ancestor? Did Christianity spring from Judaism and, if so, when? Why did the final cut between the two take place? Did Christianity replace Judaism? If so, how can the relationship between them now be described? Before interaction between the two religions is possible, an honest and unbiased attempt to understand each other must be mutual. This is a painful and difficult exercise as Christians and Jews seem to have been at odds since forever. This publication is not the final word on the relationship, but perhaps it serves as an invitation to Jews and Christians for peaceful engagement.